A Critical Assessment of the Marugoto: The Language and Culture of Japan Series of Course-books - Farzaneh Moradi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This paper is an introduction to and a critical assessment of “Marugoto” course-books comprised of 9 volumes for elementary and intermediate education of Japanese language which is provided by “The Japan Foundation” based on the standards of this foundation, split into (Starter, Elementary, Pre-intermediate, and Intermediate) levels. This study is an attempt to identify the strengths and weaknesses of this series. This critical assessment is carried out from visual and content-based aspects using Razi’s (2009) evaluation criteria. The results suggested that while having their strengths and advantages, the books suffer from a few shortcomings, which can be eliminated in future editions to achieve better results and to secure a spot as a relatively new textbook for teaching the Japanese language. However, the overall conclusion from the analysis is that despite a few problems, the strengths of the book exceed its weaknesses, and in conclusion, it can be used as a reliable source where the main aim of learning the Japanese language is acquiring speaking skills.